COMPETITIVENESS OF AGRICULTURAL PRODUCTS ON THE MEAT- DAIRY CHAIN - Sorin CHELMU, Sergiu (Economics of Agriculture, 2012)
The paper represents an analysis regarding the competitiveness of agricultural products on the meat-diary chain from Romania. Livestock sector is an important sector of national economy in general and agriculture in particular, providing raw material for food and feed people. Revitalizing agriculture is difficult or even impossible without the development of livestock sector, by reconsidering the role and place that this sector must hold in the national economy. Livestock sector is going through a difficult situation due to several factors: increased production costs caused by import competition, increased feed prices. With our accession to the EU livestock development will be determined by several factors whose combined action leads to the development of animal production imposed standards. Achieving these standards will certainly ensure Romanian agriculture development in general and livestock in particular.